Emocjonalność języka w wystąpieniach Fernanda Vallejo w obronie zwierząt - Curzytek, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses the emotional linguistic resources used by the Colombian writer Fernando Vallejo in his discourse on the defence of animals. The theoretical background includes two main contemporary approaches in the defence of animals and Vallejo`s argumentation is presented. Secondly, emotional resources related to the lexical level and oral resources related to the syntactic level are analysed in four of his speeches. The paper proves that emotionality used together with an apparent scientific argumentation reinforces rather than weakens the discourse and is one of the main elements of Vallejo`s approach to the topic.
Keywords: prawa zwierząt; emocje; etyka; bioetyka; Vallejo, Fernando (pisarz kolumbijski; 1942- )